2020
DOI: 10.9734/jpri/2020/v32i830473
|View full text |Cite
|
Sign up to set email alerts
|

The Outpatient Prescribing Pattern of Cefuroxime in Al-Kharj

Abstract: Introduction: Several previous studies reported a high prescribing rate of cephalosporin antibiotics such as cefuroxime. The inappropriate outpatients prescribing of cefuroximeleads to the development of bacterial resistance. Aim: This study was conducted to demonstrate the prescribing pattern of cefuroxime in the outpatient setting in Alkharj. Methodology: This retrospective study was conducted to know the prescribing pattern of cefuroxime. The data were collected from electronic prescriptions in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…No pharmacy and therapeutic committee to oversee the use and prescribing practices of antibiotics, and lack of practice of sensitivity testing before prescribing antibiotics contribute to inappropriate prescribing of antibiotics.” Butt et al (2017) divided diagnosis into two types—1 in which antibiotics are indicated (bacterial infections) and diagnosis for which antibiotics are not indicated (viral infections)—through expert opinions, and they studied upper respiratory tract infection prescribing patterns of antibiotics in Qatar and found that 45% ( n = 75,733) of antibiotics prescribed are deemed inappropriate least in the emergency department with 2% and were the highest for family physicians. Shaheen et al (2018) measured appropriateness by comparing prescriptions with WHO guidelines on recommendation for acute respiratory tract infections in Saudi Arabia and stated, “Many physicians in Makkah Al Mukarramah are not following the WHO guidelines for Acute Respiratory Infection.” Ahmed et al studied the outpatient prescribing pattern of cefuroxime, doxycycline, ciprofloxacin, and metronidazole in Saudi Arabia and concluded that a high percentage of antibiotics prescribed is inappropriate, and doxycycline is appropriately prescribed in the outpatients ( Ahmed, 2020a ; Ahmed, 2020b ; Ahmed, 2020c ; Ahmed, 2020d ).…”
Section: Results and Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…No pharmacy and therapeutic committee to oversee the use and prescribing practices of antibiotics, and lack of practice of sensitivity testing before prescribing antibiotics contribute to inappropriate prescribing of antibiotics.” Butt et al (2017) divided diagnosis into two types—1 in which antibiotics are indicated (bacterial infections) and diagnosis for which antibiotics are not indicated (viral infections)—through expert opinions, and they studied upper respiratory tract infection prescribing patterns of antibiotics in Qatar and found that 45% ( n = 75,733) of antibiotics prescribed are deemed inappropriate least in the emergency department with 2% and were the highest for family physicians. Shaheen et al (2018) measured appropriateness by comparing prescriptions with WHO guidelines on recommendation for acute respiratory tract infections in Saudi Arabia and stated, “Many physicians in Makkah Al Mukarramah are not following the WHO guidelines for Acute Respiratory Infection.” Ahmed et al studied the outpatient prescribing pattern of cefuroxime, doxycycline, ciprofloxacin, and metronidazole in Saudi Arabia and concluded that a high percentage of antibiotics prescribed is inappropriate, and doxycycline is appropriately prescribed in the outpatients ( Ahmed, 2020a ; Ahmed, 2020b ; Ahmed, 2020c ; Ahmed, 2020d ).…”
Section: Results and Findingsmentioning
confidence: 99%
“…Cephalosporins are widely prescribed in outpatient settings in the Gulf region. Overall, 30–40% of all antimicrobials prescribed in the Gulf region are cephalosporins with few exceptions ( Senok et al, 2009 ; John et al, 2014 ; Al-Balushi et al, 2014 ; Al Alawi et al, 2015 ; al Salman et al, 2016 ; Oqal et al, 2015 ; Alshakka et al, 2016 ; Butt et al, 2017 ; Shaheen et al, 2018 ; Alanazi, 2018 ; Almasoudi et al, 2019 ; Alanazi et al, 2019 ; Ahmed, 2020c ). Highly prescribed cephalosporins are ceftriaxone and cefuroxime.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study also showed that most of the patients received azithromycin for 3 days (88.17%) [30]. Among the 316 Outpatient who received cefuroxime in a Public Hospital in Al-kharj, the majority of cefuroxime prescriptions include tablet dosage form (81.96%) and about 62.03% of the outpatient prescriptions were prescribed by the emergency department [31]. Regarding the prescribing of metronidazole in the Outpatient Setting of a Public Hospital in Al-kharj, most of metronidazole prescriptions were regular and were prescribed mainly by residents [32].…”
Section: Antibiotics Usementioning
confidence: 87%
“…Another studies about the use of azithromycin, cefuroxime, and metronidazole were conducted [30][31][32]. From January 2018 to June 2018, 541 outpatients received azithromycin mainly as a suspension (55.64%) [30].…”
Section: Antibiotics Usementioning
confidence: 99%